The calculation of heat losses of single and twin preinsulated pipe systems in accordance with PN-EN 13941-1. Part 1: Methodology and assumptions - Kręcielewska, Ewa; Starobrat, Artur; Iwko, Ireneusz (Instal, 2024)
The article describes a method for calculating heat losses of single and twin preinsulated pipe systems as presented in PN-EN 13941-1. An attempt was made to systematize the actions during the calculations, and possible sources of essential data were identified. Examples of heat loss calculations in single pipelines with the same or different insulation thicknesses on supply and return, as well as in twin pipelines, are included. Finally, a comparative summary of the calculations performed is presented.
Keywords: district heating preinsulated pipes; heat losses